Measuring Junior High School Compliance in Providing Religious Education Services in West Denpasar - Rusmayani, Rusmayani; Libriyanti, Yuyun (Tribakti: Jurnal Pemikiran Keislaman, 2022)
Student diversity at junior high schools in West Denpasar is very heterogeneous. This diversity must be facilitated through religious services in schools. This study aims to determine the religious education services of junior high schools in West Denpasar. The method used was a survey with a sample of seven junior high schools. The data were collected by means of a questionnaire. The survey results show that the availability of religious education services for 6 junior high schools in West Denpasar has a percentage above 80% of the dimensions of the availability of religious education teachers, the dimensions of facilities and infrastructure, and the dimensions of the religious learning process. The results of the survey which stated that 16.67% of the unavailability of religious teachers and 9.09% of schools did not provide prayer rooms for students were still considered in accordance with existing laws and regulations.